THE IMPLEMENTATION OF EMANCIPATED CURRICULUM AT AN ISLAMIC HIGH SCHOOL IN PAREPARE - Zahrah Rafidah Irwan; Geminastiti Sakkir; Asriati (International Journal of Business English and Communication, 2025)
This study aims to explore the implementation of the Emancipated Curriculum at an Islamic Senior High School in Parepare. A qualitative research design was employed. The participants of this study were teachers at MAN 2 Kota Parepare during the 2024/2025 academic year, including the P5 supervisory team and English teachers. Data were collected through observation, interviews, and documentation. The findings reveal that the Emancipated Curriculum at MAN 2 Kota Parepare has been effectively implemented by teachers through careful planning, classroom instruction, and evaluation. The curriculum has encouraged students to become more active, think critically, and enhance their knowledge and skills. Most teachers expressed positive perceptions toward the Emancipated Curriculum, noting that it provides greater flexibility in designing lessons that address students’ needs. It also promotes creativity and supports technology-integrated learning, despite some remaining challenges. Overall, the implementation of the Emancipated Curriculum has positively transformed the learning environment by granting greater autonomy to both teachers and students.